Isochromanone derivatives from the endophytic fungus Fusarium sp. PDB51F5 - Sirada Boonyaketgoson (2018)
© 2015 Elsevier Ltd. All rights reserved. One new isochromenone, fusaraisochromenone (1), and one new isochromanone, fusaraisochromanone (2), together with 11 known metabolites were isolated from the broth extract of the endophytic fungus Fusarium sp. PDB51F5. Their structures were identified on the basis of spectroscopic data and were evaluated for their cytotoxic activity.